Fuzzy Logic Traffic Lights Control (FLTLC) - Abiyev, Rahib H.; Ma'aitah, Mohammad; Sonyel, Bengi (Assoc Computing Machinery, 2017)
Fuzzy logic science is the fundamental factor of any implementation and design of an intelligent system of traffic lights controller (traffic signal control), and according to this science, many applications have been designed and sat up to emulate the circumstances and conditions of an isolated traffic junction, where this emulation provides some results that illustrates the fuzzy logic controller which has got better achievement such as neural computations in which provides a means of converting a linguistic control strategy based on expert knowledge into an automatic control strategy. Throughout the last several years, fuzzy control which based on based on fuzzy logical system has proved that is one of the most effective area in fuzzy system, principally in the major of manufacturing processes and also it has a huge importance in human brain analysis or what is called, human thinking., moreover, it is closer to natural language.
9th International Conference on Education Technology and Computers (ICETC) -- DEC 20-22, 2017 -- Barcelona, SPAIN
Keywords: Fuzzy Traffic Lights Control System; Science; Vehicles; Input; Output